2000
DOI: 10.1002/1521-4141(200009)30:9<2507::aid-immu2507>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirement of perforin and IFN-γ in CD8 T cell-mediated immune responses against B16.F10 melanoma cells expressing a viral antigen

Abstract: Perforin‐mediated lysis and secretion of IFN‐γ belong to the key effector functions of CD8 T cells. To compare the anti‐tumor activity of these two mechanisms, we used B16.F10 melanoma cells (B16GP33) expressing the cytotoxic T cell epitope GP33 and T cell receptor transgenic (TCR‐tg) mice specific for GP33 and deficient in perforin or IFN‐γ. B16GP33 tumor cells, injected either i. v. to induce experimental metastases or s. c., were similarly controlled in both wild‐type and perforin‐deficient, but not in IFN‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 24 publications
5
22
0
Order By: Relevance
“…This suggests that rapid tumor cell lysis by P14 IL-2 cells was of minor importance for tumor cell control in our model system. Elimination of B16 gp33 pulmonary metastases by activated P14 T cells requires IFN-g but does not depend on perforin-mediated cell lysis [17]. P14 IL-2 cells were efficient in IFN-g production but nevertheless failed to lower pulmonary metastases.…”
Section: Discussionmentioning
confidence: 93%
“…This suggests that rapid tumor cell lysis by P14 IL-2 cells was of minor importance for tumor cell control in our model system. Elimination of B16 gp33 pulmonary metastases by activated P14 T cells requires IFN-g but does not depend on perforin-mediated cell lysis [17]. P14 IL-2 cells were efficient in IFN-g production but nevertheless failed to lower pulmonary metastases.…”
Section: Discussionmentioning
confidence: 93%
“…To assess such a hypothesis, we monitored the tumor-specific IFN-␥ response in MT/ret melanoma mice and compared it with the response in mice with concurrent vitiligo. Many reports have indicated that IFN-␥ plays a critical role in the development of tumor immunity, and recent reports including ours using IFN-␥ knock-out mice demonstrated a crucial role for IFN-␥ in the control of B16 melanoma growth in vivo (15)(16)(17). To evaluate natural tumor-specific response, ex vivo IFN-␥-ELISPOT assays were performed by using PBLs isolated from MT/ret mice as effector cells and a Melan-ret cell line as melanoma antigen-presenting cells.…”
Section: Treatment With Heavy Metal Leads To Vitiligo Development In mentioning
confidence: 92%
“…The importance of these effector molecules in T cell-mediated tumor cell rejection has been examined by numerous studies using gene-deficient mice. Perforin-deficient mice were reported to be more susceptible to tumor development in some models [5][6][7][8], while other studies found that perforin-deficient CTL were fully capable of exerting anti-tumor activity in vivo [9][10][11][12][13]. Similarly, CD95L-dependent effector mechanisms have been shown to be important in some models [14][15][16] but not in others [9,13,17].…”
Section: Introductionmentioning
confidence: 99%
“…An early study in mice revealed that rejection of pulmonary metastases by cultured tumorspecific CD8 T cells correlates better with their capacity to produce IFN-c than with their cytotoxicity in vitro [18]. More recent studies using IFN-c-deficient mice have provided compelling evidence for the important role of IFN-c in T cell-mediated tumor cell rejection [7,9,10,13,14,[19][20][21][22][23][24][25][26]. Various possibilities can be envisaged to explain the anti-tumor activity of IFN-c: first, IFN-c is known to increase MHC expression and antigen presentation, thereby rendering tumor target cells more susceptible to CTL attack [27][28][29].…”
Section: Introductionmentioning
confidence: 99%